Additive manufacturing of the high-strength and low modulus biomedical Ti-10 Nb alloy under reactive atmosphere. (December 2022) - Zhang, J.W.; Dong, Y.P.; Tang, J.C.; Wang, D.W.; Lu, W.J.; Li, Y.L.; Wang, D.Y.; Okulov, I.; Yan, M.
Abstract: In situ enhancement of alloy properties via additive manufacturing is a convenient and promising approach that is attracting increasing attention. Herein, we overcame the insufficient strength of Ti-10 Nb alloy used in orthopedic implants by introducing an Ar + N2 reactive atmosphere during selective laser melting. The mechanical properties, phase compositions, microstructures, and biocompatibility of the Ti-10 Nb alloys formed under the reactive atmospheres containing 3 vol% and 5 vol% N2 were investigated. Scanning electron microscope, electron backscatter diffraction, and transmission electron microscope were employed to investigate the mechanism of N on the mechanical property evolution of Ti-10 Nb. The biocompatibility of the Ti-10 Nb alloys fabricated under different N2 concentrations was investigated using in vitro cell proliferation and adhesion assays, with pure Ti used as a reference. The Ti-10 Nb alloy displayed a tensile strength of 855 MPa, yield strength of 763 MPa, an elongation of 21.6%, and elastic modulus of 72 GPa when the N2 fraction was 3 vol%. The as-printed Ti-10 Nb alloy exhibited good biocompatibility, and the introduction of N promoted the proliferation of MG-63 cells. This study paves the way for the synthesis of high-strength and low modulus biomedical Ti alloys by reactive additive manufacturing. Graphical Abstract: ga1